Critical thinking in degrees of pedagogy - Pedraja-Rejas, Liliana; Rodríguez-Ponce, Emilio; Ganga-Contreras, Francisco (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
This article aims is to review the variables: characteristics of the academic body, development of critical thinking in students and educational outcomes, in order to establish, from a conceptual and empirical perspective, relationships between these variables. For this purpose, secondary sources are used, preferably theoretical discussion articles and empirical studies from mainstream journals. As a result of the research, a model is constructed that relates, both directly and indirectly, the characteristics of the academic body, the development of critical thinking in students and educational outcomes in initial teacher training.